(untitled) (Research, Society and Development, 2022)
Parmesan cheese is consumed by the population in grated form, which has provided a greater choice of product brands on the market. However, cheese is a product susceptible to contamination, offering risks to public health. Few studies on this subject have been published in the literature, making it important to check the quality of products available on the market. Thus, the work aimed to evaluate the microbiological quality, determine the moisture content and the profile of volatile compounds of different packaged and bulk samples of grated parmesan cheese, available on the market, checking if the products meet the standards established by legislation. Regarding moisture, it was observed that 50% of the samples presented values ​​above the permitted (20 g/100 g). In the microbiological analysis it was found that 70% of the samples were unfit for consumption with counts above those allowed by the legislation for molds and yeasts, Staphylococcus spp. and total coliforms. In some samples the presence of thermotolerant coliforms and Escherichia coli were identified, but they did not exceed the standard established by legislation. The analysis of volatile compounds allowed the identification of 31 compounds from different classes such as ketones (7), esters (7), carboxylic acids (6), aldehydes (4), alcohols (2), lactones (2), aromatic hydrocarbons (1), terpene (1) and triacetin (1). There was a variation in the chemical composition between packaged and bulk cheeses. These variations can be observed in the lack of uniformity of the samples, which requires the need for more efficient inspection by official bodies and improvements in hygienic conditions during manufacturing.